HEAT FLOW IN KIMBERLITE PROVINCES OF ANCIENT PLATFORMS - Duchkov A.D.; Puzankov Yu.M.; Sokolova L.S. (My University, 1999)
Geothermal data on six kimberlite provinces of ancient platforms in Siberia, Africa, North America, and South America are considered. The intensity of heat flow there varies from 10-18 to 62-100 mW/m2, averaging 46-54 mW/m2. These average values are in concordance with conductive geotherms obtained by thermobarometry of mineral associations from deep-seated xenoliths from kimberlite pipes. The only exclusion is the Yakutian kimberlite province in the east of the Siberian Platform, where the intensity of measured heat flows (20-30 mW/m2) is considerably lower than that calculated for the time of kimberlite formation (35-40 mW/m2). This anomaly may be related not to the climate cooling but to a decrease in the intensity of radiogenic heat generation in the Earth's crust and shielding of mantle heat flow. This is suggested from the occurrence of kimberlite fields within the protrusions of the lower crust with minimum contents of radioactive elements in its rocks.